Governments and Promised Fiscal Consolidations : Do They Mean What They Say? - Gupta, Sanjeev (IMF Working Papers; Working Paper, 2017)
This paper analyses the causes and consequences of fiscal consolidation promise gaps, defined as the distance between planned fiscal adjustments and actual consolidations. Using 74 consolidation episodes derived from the narrative approach in 17 advanced economies during 1978 - 2015, the paper shows that promise gaps were sizeable (about 0.3 percent of GDP per year, or 1.1 percent of GDP during an average fiscal adjustment episode). Both economic and political factors explain the gaps: for example, greater electoral proximity, stronger political cohesion and higher accountability were all associated with smaller promise gaps. Finally, governments which delivered on their fiscal consolidation plans were rewarded by financial markets and not penalized by voters.